Epitaxial graphene/silicon carbide intercalation: a minireview on graphene modulation and unique 2D materials. Issue 33 (8th August 2019) - Briggs, Natalie; Gebeyehu, Zewdu M.; Vera, Alexander; Zhao, Tian; Wang, Ke; De La Fuente Duran, Ana; Bersch, Brian; Bowen, Timothy; Knappenberger, Kenneth L.; Robinson, Joshua A.
Abstract : Intercalation of atomic species through epitaxial graphene on silicon carbide began only a few years following its initial report in 2004. Abstract : Intercalation of atomic species through epitaxial graphene on silicon carbide began only a few years following its initial report in 2004. The impact of intercalation on the electronic properties of the graphene is well known; however, the intercalant itself can also exhibit intriguing properties not found in nature. This realization has inspired new interest in epitaxial graphene/silicon carbide (EG/SiC) intercalation, where the scope of the technique extends beyond modulation of graphene properties to the creation of new 2D forms of 3D materials. The mission of this minireview is to provide a concise introduction to EG/SiC intercalation and to demonstrate a simplified approach to EG/SiC intercalation. We summarize the primary techniques used to achieve and characterize EG/SiC intercalation, and show that thermal evaporation-based methods can effectively substitute for more complex synthesis techniques, enabling large-scale intercalation of non-refractory metals and compounds including two-dimensional silver (2D-Ag) and gallium nitride (2D-GaN x ).